Solidarité mutualiste et immigration italienne. La Fratellanza d’Aubagne et la mémoire reconstruite - Isabelle Felici (Cahiers d’histoire)
This article retraces the history of the Italian mutual benefit society La Fratellanza, founded in Aubagne, near Marseille, which celebrated its centenary in 2007. Its meetings reports are among the few texts written by the immigrants themselves. Their analysis helps to take the immigrants’ points of view and understand their choices at historic turning points. In the first place, the article examines the Italian presence in Aubagne, frequently overshadowed by that in Marseille. Then it looks after the activities of La Fratellanza during and between the two world wars, at the time of fascism and its repercussions on the lives of the members, till the 1980s, when immigrants in France started to reconstruct their Italian memory.